Prospective studies on clinical outcomes of Lichtenstein’s tension free inguinal hernioplasty under local anaesthesia - Brar, Navjot; Singh, Amanjot; Bajwa, Rajbir (International Surgery Journal, 2017)
Background: Inguinal hernia may be generally defined as a protrusion of viscus or part of a viscus though inguinal canal. The only way recommended to treat inguinal hernias now a day is to perform tension free Lichenstein repair. In this study, we have done a prospective study on clinical outcomes of lichtenstein tension free inguinal hernioplasty under local anaesthesia in Department of General Surgery, Sri Guru Ram Dass Hospital and Research, Sri Amritsar from 15 August 2014 to 15 February 2017, a period of 2 and half years. Methods: A prospective study was conducted in patients admitted in wards with inguinal hernia from General Surgery Outpatient Department. The series consisted of 60 patients between 15 to 74 years. Results: It is found that no recurrence has yet occurred in 2½ years follow up and it is well accepted specially in older age group (55 -74 years). Conclusion: The methods of Lichtenstein’s tension free inguinal hernioplasty under local anaesthesia is safe, simple, effective, economical, and without any side effects such as hypotension, nausea, vomiting, urinary retention, and spinal headache.